Fish, Characiformes, Characidae, Astyanax turmalinensis Triques, Vono and Caiafa, 2003: distribution extension - Mauro Triques; Frederico Queiroz (Check List, 2010)
Astyanax turmalinensis was described from upper Jequitinhonha River basin and this note extends the species distribution to two adjacent drainages, the São Francisco and the Doce River basins, in the Parque Nacional da Serra do Cipó.